Salivary IgA in chronic kidney disease patients undergoing hemodialysis in Missan governorate - Abid Hatem, Faris; Mohammad, Zaheda J (Journal of Baghdad College of Dentistry, 2015)
Background: Chronic kidney disease is a worldwide health problem, with adverse outcomes of cardiovascular disease and premature death, can be divided into five stages, depending on how severe the damage is to the kidneys, or the level of decrease in kidney function, the final stage of chronic kidney disease is called end-stage renal disease, salivary immunoglobulin A is the main immunoglobulin found in mucous secretions, including tears, saliva, colostrum and secretions from the genitourinary tract gastrointestinal tract, prostate and respiratory epithelium . It is also found in small amounts in blood.This study aimedto measuresalivary flow rate and salivaryimmunoglobulin Alevels in chronic kidney disease patients on hemodialysis treatment in comparison with healthy control subjects.Materials and Methods: Ninety (90) subjects were participated in this study; 45 Patients undergoing hemodialysis with chronic kidney diseases; 45 health control subjects. Saliva collected was measured and levels of salivary immunoglobulin A were measured by Enzyme Link Immunosorbent Assay (Elisa).Results:The present studyrevealed that the mean value of salivary flow rate in chronic kidney disease patients was (0.34 ± 0.19) ml/min, while for healthy control subjects was (1.02 ± 0.39) ml/min, there wasstatisticallysignificantly decrease in salivary flow rate ofchronic kidney disease on hemodialysis patients as compared to control healthy subjects.The present study revealed that the (Mean±SD) of the immunoglobulin A in chronic kidney disease patients on hemodialysis (388.81±227.86) µg./ml, while in control group (273.98±155.89) µg./ml, the result revealed statistically significant increase in chronic kidney disease patients on hemodialysis as compared to control subjects.Conclusions: Salivary immunoglobulin (IgA) reflects the functional capacity of the glands. Increased concentration of this component is usually marker of a poor general condition.